Study of Micro-Explosion Phenomena of Various Water-in-Biodiesel Emulsion (WiBE) Using Visualization Technique - Hussein Shah, Mohamad Izzudin (IRC, 2016)
The main purpose of this Final Year Project (FYP) is to ascertain the micro-explosion phenomena occurrence in various blends of Water-in-Biodiesel Emulsion (WiBE) using visualization technique. Micro-explosion phenomena are dependent on the type of emulsion blends such as, water content, surfactant concentration, water particle, viscosity and density. In addition, the temperature of the hot plate to achieve Leidenfrost effect of the emulsion droplet also affects the occurrence of the micro-explosion. The WiBE samples used for this project were blended based on the water content, surfactant concentration and hydrophilic-lipophilic balance (HLB) value. The preparation matrix of a stable WiBE samples were retrieved from a previous micro-explosion research experiment which consisted of six samples. The samples were produced by blending together in an electrical blender or mechanically stirred with a constant speed of 1500 rpm for a period of fifteen (15) minutes. The water particles were observed with Olympus BX51 microscope at 500x magnification.